A model for the fast evaluation of prompt losses of energetic ions in stellarators. (14th October 2021) - Velasco, J.L.; Calvo, I.; Mulas, S.; Sánchez, E.; Parra, F.I.; Cappa, Á.; the W7-X Team,
Abstract: A good understanding of the confinement of energetic ions in non-axisymmetric magnetic fields is key for the design of reactors based on the stellarator concept. In this work, we develop a model that, based on the radially-local bounce-averaged drift-kinetic equation, classifies orbits and succeeds in predicting configuration-dependent aspects of the prompt losses of energetic ions in stellarators. Such a model could in turn be employed in the optimization stage of the design of new devices.